Collocational Processing in L1 and L2: The Effects of Word Frequency, Collocational Frequency, and Association. Issue 1 (11th August 2020) - Öksüz, Doğuş; Brezina, Vaclav; Rebuschat, Patrick
Abstract: This study investigated the effects of individual word frequency, collocational frequency, and association on L1 and L2 collocational processing. An acceptability judgment task was administered to L1 and L2 speakers of English. Response times were analyzed using mixed‐effects modeling for 3 types of adjective–noun pairs: (a) high‐frequency, (b) low‐frequency, and (c) baseline items. This study extends previous research by examining whether the effects of individual word and collocation frequency counts differ for L1 and L2 speakers' processing of collocations. This study also compared the extent to which L1 and L2 speakers' response times are affected by mutual information and log Dice scores, which are corpus‐derived association measures. Both groups of participants demonstrated sensitivity to individual word and collocation frequency counts. However, there was a reduced effect of individual word frequency counts for processing high‐frequency collocations compared to low‐frequency collocations. Both groups of participants were similarly sensitive to the association measures used. Abstract :